New “racialised” geographies of kinship. Kinning in Mixed families - Rosa Parisi (Antropologia)
Mixed families, in Europe as in Italy, constitute a rapidly expanding phenomenon. This essay analyses the way in which extraneousness-otherness are embodied in the kinning of the mixed couples involved. The paper is divided into two sections; in the first, we will discuss how the kinning process related to migratory regimes acts as a device for the differentiation of family and national belonging; in the second, we will analyse the family mixedness in action in the kinning process of mixed family particularly of Italian-Moroccan families. This section will be focused especially how different attitudes and ways of dealing with the visible somatic trace of the child born in mixed family are part of kining process.